P128 Cardiovascular Effects of Statin Therapy on Arterial Stiffness in Patients with COPD: A Double Blind Randomised Controlled Trial. (14th November 2013) - John, M; Cockcroft, JR; McKeever, TM; Harrison, TW; Shale, DJ; Thornton, JG; Knox, AJ; Bolton, CE
Abstract : Background: As cardiovascular disease is a comorbidity and major cause of death in patients with COPD, primary preventative strategies are required. Arterial stiffness, as measured by aortic pulse wave velocity (PWV) is increased in patients with COPD 1, and is an independent predictor of cardiovascular risk 2, which is modifiable over the short term. We hypothesised that aortic PWV, would be reduced by six weeks treatment of simvastatin 20mg once daily compared to placebo in selected patients with COPD without concurrent heart disease, diabetes or hypercholesterolemia. Methods: Clinically stable patients with confirmed COPD were recruited and randomised to either simvastatin 20mg od (active) or placebo in double blinded fashion. Aortic PWV, blood pressure, spirometry, six minute walking distance, and lipids were measured pre- and post- 6 weeks treatment. Primary analysis compared PWV between groups. A predefined subgroup analysis compared those with a baseline PWV≥10m/s. Results: The patients were well matched for age, sex, smoking and lung function; active, n = 33 and placebo, n = 37. The recruitment target was met. Compliance was high with the active group achieving significantly lower total cholesterol - between arms mean (95% CI): -1.1 (-1.3, -0.8)mmol/L, p < 0.001. There was no significant change in aortic PWV after treatment in the active compared to placebo group: -0.7 (-1.8, 0.5)m/s, p = 0.24, In the subgroup with aortic PWV≥10m/s, n = 22, aortic PWV improved in the active arm compared to placebo: -2.8 (-5.2, -0.3)m/s, p = 0.03. This latter difference remained statistically significant after adjusting for age and sex. Blood pressure, lung function and six minute walking distance did not change. Conclusions: In this pilot study, despite a significant reduction in total cholesterol there was no improvement in aortic PWV in patients with COPD taking simvastatin 20mg compared to placebo over 6 weeks. The positive findings in the subgroup with a higher baseline aortic PWV warrants further studies in high risk patients to confirm the impact of statin use on the cardiovascular outcome of COPD. Trial reference: NCT01151306 Supported by NIHR RfPB grant References: Sabit, R., et al ., Am J Respir Crit Care Med, 200;175 :1259–65 Laurent, S., et al ., Eur Heart J, 2006; 27 :2588–605